Feedback loops in translating medical documents in light of Skopos theory and text types theory - Sadoun, Nadjet (The International tax journal, 2026)
This article explores the role of feedback loops in the translation of medical documents, focusing on Skopos Theory and text types. It examines how translators utilize feedback to ensure accuracy and effectiveness in conveying medical terminology across languages. Key concepts include understanding text types and adapting translation strategies accordingly, enhancing communication in specialized domains. The study emphasizes the dynamic interaction between translators, document recipients, and feedback mechanisms, crucial for achieving precise medical document translations.